Tingkat Kerentanan Lingkungan Pesisir Selatan Kabupaten Bangkalan Terhadap Potensi Tumpahan Minyak (Oil Spill) [Level of South Coastal Area of Bangkalan Residence on Oil Spill Potention] - Maulinna K Wardhani, Sulistiono, Vincentius P Siregar (Faculty of Fisheries and Marine Universitas Airlangga, 2011)
AbstractThe South Coastal Area of Bangkalan Residence is a dynamic area with potention of oil spill pollution. These are showed that activation of port construction, the activity of mining and other infrastructures. The aim of the research was to determine sensitivity level of South Coastal Area of Bangkalan Residence on oil spill potention as one of mitigation effort. In generally, the result of environment sensitivity index showed that South Coastal Area of Bangkalan Residence is a sensitivity area on oil spill.